“Mosaico étnico”: uma análise de discursos que constroem classificações para a população do Paraná (1953-2015) - Santos, Raiane Clair Ramirez dos (2017)
In this paper, we discuss discourses that aim to build an identity for the State of Paraná as a "mosaic of ethnicities", a "land of all people". The dissertation is divided into three chapters. In the first, we analyze the magazines Ilustração brasileira; Álbum do 1°Centenário de Emancipação Política do Paraná; Exposição Internacional do Café e Feira de Curitiba; Boletim da Câmara de Expansão Econômica do Paraná (edição comemorativa do centenário do Paraná, all published in 1953, due to the celebrations of the first centenary of political emancipation of Paraná; In the second, we analyze volumes I and III of the collection História do Paraná, published in 1969; And in the third we analyzed interview conducted in 2015 with members of folk groups associated with AINTEPAR – Associação Interétnica do Paraná. These three supports - magazines, books and interviews - from different contexts present speeches that classify Paraná as a "Diferent Brazil" and its population as white, European, "peaceful, orderly, hospitable and hardworking". For the analysis of such discourses, we start from the theoretical perspective proposed by Stuart Hall, who understands that identities are not static and fixed substances, but produced within discourses. The three supports - magazines, books and interviews - analyzed in this work, in different contexts, present speeches that classify Paraná as a "Brazil Diferente" and its population as white, European, "peaceful, orderly, hospitable and working". It is the construction of an identity for the population of Paraná that is intended univocal and fixed, but which is fluid. This fluidity is most evident in the interviews with dancers of folk groups, analyzed in the third chapter.